Negative Information: Statement of Fact or Expression of Opinion? - O. V. Kukushkina (Теория и практика судебной экспертизы, 2016)
The paper explores the key problems of establishing the type of negative information and differentiating between facts and opinions. This is one of the most challenging problems of forensic linguistics that requires a robust methodological framework to be tackled successfully. When faced with this problem, the expert has to deal with the ambiguity of terminology and wording of questions, as well as the complexity of the object of study – the semantics of statements encountered in acts of speech. The paper analyzes the content of key terms traditionally used to address this forensic problem, and offers a possible solution. The so-called “factual square” is a method based on analyzing a statement against four semantic parameters: presence of statement of past action; verifiability of this statement on the basis of specificity of description of the action and its potential observability; lack of alternative, i.e. indication of a different possibility; the purpose of conveying negative information. The paper also analyzes the basic types of factual information and offers specific examples of semantic analysis of statements using the proposed approach.